Rancang Bangun Alat Destilator Pengubah Limbah Tempurung Kelapa Menjadi Asap Cair dan Pengubah Arang dari Batok Kelapa - Rio Akmamul Cahya Kusuma; Fipka Bisono; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The high yield of coconut in Indonesia is positively related to the production of coconut shell waste which is difficult to decompose by microorganisme. Therefore, in recent years a method of utilizing coconut shell waste for charcoal and liquid smoke has been developed. So far, the process of making liquid smoke from coconut fiber (coconut coir liquid smoke) is usually carried out for 3-5 days and the amount of liquid smoke is very small. The use of liquid smoke is also adapted to clarify the qualities of liquid smoke, is used as a wood preservative and thickener, as an antimicrobial agent, and as a natural food preservative. In addition, e-liquid can also be used as a natural preservative for food, meat, and fish, it is also very suitable to be used as a natural substitute for formalin or borax for insect repellent, and a wood preservative which has received wide attention in recent years. Therefore, the purpose of this research is to design a device that produces liquid smoke from burning coconut shells from the distillation process, which can increase the amount of liquid smoke produced.